DAKWAH PADA MASYARAKAT PERKOTAAN - Iskandar Iskandar (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
Dakwah is a religius phenomenon which is ideal normative as well as social phenomenon which rational, actual and empirical as sunnatullah. In the other hand dakwah is righteous deeds (syariah and moral) that comes from faith (aqidah), taqwa (appreciation of divinity) which must be implemented and understood by the humans in science, in order that dakwah have to in step with modern world. Urban society has been from the personality of its members which to rely more on the ability of a yourself than others. It means that urban society had more capibility than others societs outside, in material or immaterial.